Evaluating human assets in organizations: a proposal for a literature review - Pimenta, Cristovão Sá; Proença, Maria Teresa (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Human Capital (HC) has been recognized as a decisive fator in the performance of organizations, influencing the results obtained and even the market value of organizations. However, how this intangible asset can be demonstrated and highlighted, remains open to discussion. If highlighted in the financial statements of organizations, one could safely and accurately say that people are an organization’s greatest asset. Furthermore, the need to measure Intellectual Capital (IC) and HC has been profusely discussed. If, on the one hand, a consensus on the acceptability of the measurement has not been difficult to achieve, on the other a consensus about what and how to measure it is not a straightforward task. We intend to discuss how to measure/evaluate HC, considering the needs of the financial accounting system, the need to manage people more effectively, and the need for a proper evaluation and appreciation of organizations in the market. Thus, this article defines our field of research and proposes a revision of some literature on the field of our investigation.